Analisis Kinerja Keuangan dan Tingkat Kemandirian Pemerintahan Kabupaten dan Kota Cirebon - SEPTIANI, TIKA (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2018)
The implementation of the unsettled regional autonomy, require local governments to put greater attention on performance management of the finance area. The level of independence of local Government can be reflected in the financial management area is good, accountable and transparent, therefore needed financial performance measurement to assess the accountability of the Government. This research using secondary data obtained from Badan Pemeriksa Keuangan (BPK) Representatives in West Java. The type of Data that is used in the form: Pendaatan the original Data areas, Data revenues, Routine Shopping Data, and Data development spending Kabupaten dan Kota Cirebon.. Methods of analysis used in this study is the analysis of the ratio of the Financial Independence of the region, the ratio, the ratio of effectiveness of activity, and the ratio of Growth to know the regional financial management performance and independence Kabupaten dan Kota Cirebon. Based on the results of the analysis and discussion of which has been described, the average performance of financial management and the level ratio of the Financial Independence of kabupeten and kota Cirebon on the basis of the analysis of financial ratios is good. It is visible from the ratio of the Financial Independence kabupeten and kota Cirebon who despite having average still low i.e. by 25%, but overall the ratio of independence has experienced an increase of years up to the year 2013 2015.